EXPOSURE OF INFORMATION, FAMILY KNOWLEDGE OF DENGUE HEMORRHAGIC FEVER, AND BEHAVIORS IN IMPLEMENTING ERADICATION OF MOSQUITO NESTS IN SIDOARJO - Meli Diana; Riesmiyatiningdyah Riesmiyatiningdyah (Nurse and Health: Jurnal Keperawatan, 2020)
Dengue Hemorrhagic Fever is an infectious disease caused by one of four dengue viruses that is transmitted by mosquitoes, especially aedes aegypti and aedes albopyctus. The occurrence of outbreaks in Indonesia caused by various factors, including an environment that is still conducive to the breeding of Aedes mosquitoes, expansion of endemic areas due to the emergence of new residential areas, minimal eradication of mosquito nests, and increased population mobilization.This correlational study uses cross sectional method where the data collection is by distributing questionnaire. The number of samples in this study were three hundred (300) respondents who were drawn using stratified random sampling technique. After the data is collected then tabulated and processed using the Spearman Rho Test with p ≤ 0.05.The statistical test results of the relationship between the level of knowledge and behavior in mosquito nests eradication using the Spearmen rho test showed that p-value = 0.882> α so that it was concluded that there was no relationship between them. While the statistical test results of the relationship between information exposure and behavior mosquito nests eradication using the Spearmen rho test found that there was no relationship between the two variables p value = 0.229> α so it was concluded that there was no relationship between them.The community must be active in seeking information about dengue hemorrhagic fever and increase their participation in eradicating mosquito nests on an ongoing basis both at home and in the surrounding environment. Keywords: Information, Knowledge, DHF, PSN Behavior